Free radial forearm adiposo-fascial flap for inferior maxillectomy defect reconstruction - Krishnakumar Thankappan; Nirav P. Trivedi; Mohit Sharma; Moni A. Kuriakose; Subramania Iyer (Indian Journal of Plastic Surgery)
A free radial forearm fascial flap has been described for intraoral reconstruction. Adiposo-fascial flap harvesting involves few technical modifications from the conventional radial forearm fascio-cutaneous free flap harvesting. We report a case of inferior maxillectomy defect reconstruction in a 42-year-old male with a free radial forearm adiposo-fascial flap with good aesthetic and functional outcome with minimal primary and donor site morbidity. The technique of raising the flap and closing the donor site needs to be meticulous in order to achieve good cosmetic and functional outcome.